Looking up! : the science of stargazing - Rao, Joe (Science of fun stuff., 2017)
Provides trivia on the planets, the Sun, and other celestial bodies, including the temperature on the surface of the Sun, why Pluto is considered a dwarf planet, and when and where one can see the next total solar eclipse.